Green intellectual capital, green HRM and green social identity toward sustainable environment : a new integrated framework for Islamic banks - Muhammad, Ali; Chin Hong, Puah; Anum, Ali; Syed Ali, Raza; Norazirah, Ayob (Emerald Publishing Limited, 2022)
Purpose – The role of green human resource management in Islamic banking remains relatively unexplored. This study focuses on how green human resource management plays a part using intellectual capital and how green human resource improves employee commitment, eco-friendly behavior and environmental performance in Islamic banks. Design/methodology/approach – This paper integrated two well-established theoretical frameworks, namely, intellectual capital-based view theory and social identity theory. A survey-based research instrument was employed to collect sample data of 231 respondents. To test hypotheses, we considered partial least square structural equation modeling (PLS-SEM)-based approach using SmartPLS. Findings – The results indicate that green human capital, green structural capital and green relational capital significantly influenced green human resource management. Similarly, green human resource management showed a significant positive impact on employee commitment, eco-friendly behavior and environmental performance. Moreover, this study found significant positive results on the interrelationship between employee commitment, eco-friendly behavior and environmental performance. The outcomes recommend that Islamic bank HR managers and top management should strengthen green human resource management policies. Additionally, the Islamic bank HR department should consider bank intellectual capital and employee social identity while making environment-friendly policies. Originality/value – This study provides novel contributions by offering some useful guidelines to Islamic bank managers and practitioners. In addition, our research aids general green human resource literature and adds value to promoting a sustainable organization.